2012
DOI: 10.1097/ta.0b013e318267cd80
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of adverse drug events and cost savings associated with PharmD interventions in an academic Level I trauma center

Abstract: Economic analysis, level III; therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 28 publications
0
55
0
1
Order By: Relevance
“…Future studies are needed in this direction, as ADRs could also happen with DDIs. [14] There was no incidence of failure to receive therapy; this can be attributed to the fact that especially for the ICU patients, the drugs were not charged as it was a charity hospital (which eliminates the financial aspect) and all the medicines are administered by the nurses (which eliminates the patient adherence problems).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are needed in this direction, as ADRs could also happen with DDIs. [14] There was no incidence of failure to receive therapy; this can be attributed to the fact that especially for the ICU patients, the drugs were not charged as it was a charity hospital (which eliminates the financial aspect) and all the medicines are administered by the nurses (which eliminates the patient adherence problems).…”
Section: Discussionmentioning
confidence: 99%
“…Additional input comes from ICU-based pharmacy support [92] . Pharmacists are significant drivers in ASPs, with roughly one-fifth of pharmacist intervention in an American trauma centre being ASP related [93] . The MDT approach itself seems to be more effective than purely its components.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study at a trauma centre found that clinical pharmacy activities and interventions, including discontinuation of medications, changes to antibiotic therapy, and changes from IV to oral formulations, resulted in significant cost savings, either directly or by preventing adverse drug events. 8 The current study assessed only direct and immediate medication cost savings; long-term costs were not considered. Increased health care costs due to changes to medications that might have resulted in increased costs, such as therapeutic substitutions and increases in doses, were not considered as an outcome, nor was there any attempt to associate cost savings with a particular dollar value.…”
Section: Discussionmentioning
confidence: 99%